Answer :

Given:-


(i)g={(1, 1), (2, 3), (3, 5), (4, 7)}


(ii)g(x) = αx + β


For x=1 and αx + β


g(1)=α(1)+ β=1


α+ β=1


For x=2


g(2)=α(2)- β=3


2α- β=3


Similarly with g(3) and g(4)


Using above value


α=2


β=1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

State True Mathematics - Exemplar

State True Mathematics - Exemplar

State True Mathematics - Exemplar

Let A = {1, 2, 3}Mathematics - Exemplar

Show that the relMathematics - Board Papers

Let N denote the Mathematics - Board Papers